The Impact of Competing Values as a Mediating Variable on the Relationship between Transformational Leadership and Effective Organizational Change “A Field Study on Cairo University Hospitals” - Ismail, Reda (The Arab Journal of Administration, 2020)
The aim of present research was in line with transformational theory examine the direct and indirect effect of competing values on the relationship between Transformational leadership and effective organizational change. in addition to find out the most dominant culture type In Cairo University Hospitals by using the competing value framework (CVF).To achieve those goals the researcher used Quantitative descriptive and analytical design , Data collected through questionnaires from sample of 202 employees of Cairo University Hospitals, The statistical package for social sciences (SPSS) program was used to analyze and examine the hypotheses. Empirical findings of data provides evidence to support our intended hypothesizes and revealed that there is a statistically significant impact at the level of significance (a≤0.05) between transformational leadership and effective organizational change, The results also indicated that competing values partially mediated the relationship between transformational leadership and effective organizational change (P <.01). The findings of this study recommended that the hospitals needs to adopt the concept of transformational leadership, and providing behaviors and elements of transformational leadership for its members; because it is one of the most appropriate concepts of leadership to lead the change. Also provide strategies that promote group orientation and reduced hierarchy, enhance the multidisciplinary team training and continuous quality improvement tools, and improvement human resource practices and policies; permits to express ideas empower and encourage employees to participate in decision-making and problem-solving process In a creative way; conduct training workshop to learn and improve organizational culture values and using the competing value framework (CVF) That will increase the chances of adopting the effective organizational change in the hospitals, to follow the developments in the external environment, for the purpose of making the appropriate change plans to reinforce the internal environment of the hospitals.